Superoxide and NADPH oxidase do not modulate skin blood flow in older exercising adults with and without type 2 diabetes - McGarr, Gregory; Fujii, Naoto; McNeely, Brendan; Hatam, Kion; Nishiyasu, Takeshi; Sigal, Ronald; Boulay, Pierre; Kenny, Glen (Université d'Ottawa | University of Ottawa, 2019)
Objective: High aerobic fitness may prevent age-related decrements in cutaneous vasodilation while type 2 diabetes may exacerbate this decline. The mechanisms underlying these responses remain unclear, but may be due to an excess of reactive oxygen species. We hypothesized that superoxide scavenging or NADPH oxidase inhibition would improve cutaneous vasodilation in older adults exercising in the heat, particularly in healthy low-fit individuals and those with type 2 diabetes. Methods: Twenty seven older adults were evenly separated into three groups (healthy low-fit: VO2peak = 24.4±2.4 mlkg-1min-1, 61±8 years; healthy high-fit: 42.5±9.7 mlkg-1min-1, 56±6 years; type 2 diabetes: 30.0±7.6, mlkg-1min-1, 58±7 years). The healthy low-fit and type 2 diabetes groups performed two successive 30-min cycling bouts at 65%VO2peak in the heat (35℃), separated by 30-min rest. The high-fit group cycled at the same absolute heat load (and therefore requirement for heat loss) as their healthy low-fit counterparts during the first exercise bout (Ex1) and at the same relative intensity (65%VO2peak) during the second (Ex2). Forearm cutaneous vascular conductance (CVC%max) was measured at microdialysis sites perfused with: 1) lactated Ringer’s solution (control); 2) 10 mM NG-nitro-L-arginine-methyl-ester (L-NAME, nitric oxide synthase inhibitor); 3) 100 μM apocynin (NADPH oxidase inhibitor); 4) 10 μM tempol (superoxide dismutase mimetic), with responses compared at baseline, end-Ex1, and end-Ex2. Results: In all groups, L-NAME consistently reduced CVC%max relative to the other treatment sites by ~16-21% during Ex1 and by ~22-27% during Ex2 (all P<0.05). Conversely, superoxide scavenging and NADPH oxidase inhibition did not influence CVC%max (all P>0.05). Conclusion: Superoxide and NADPH oxidase do not modulate cutaneous vasodilation in healthy low- or high-fit older adults exercising in the heat, regardless of aerobic fitness level or relative exercise intensity employed, nor do they influence cutaneous vasodilation during an exercise-heat stress in those with type 2 diabetes. However, NOS remains an important modulator of cutaneous vasodilation during exercise in all groups.
Keywords: aging; apocynin; microcirculation; reactive oxygen species; skin blood flow; tempol; thermoregulation